Restoring Occlusal Vertical Dimension of Kennedy Class I Partially Edentulous Mandibular Arch Using an Overlay Cobalt-Chromium Partial Denture and Thin Acrylic Veneers - Wan Nor Syariza Wan Ali; Hazira M Yusof (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)